If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(14x + 7) + -6 = 0 Reorder the terms: -1(7 + 14x) + -6 = 0 (7 * -1 + 14x * -1) + -6 = 0 (-7 + -14x) + -6 = 0 Reorder the terms: -7 + -6 + -14x = 0 Combine like terms: -7 + -6 = -13 -13 + -14x = 0 Solving -13 + -14x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '13' to each side of the equation. -13 + 13 + -14x = 0 + 13 Combine like terms: -13 + 13 = 0 0 + -14x = 0 + 13 -14x = 0 + 13 Combine like terms: 0 + 13 = 13 -14x = 13 Divide each side by '-14'. x = -0.9285714286 Simplifying x = -0.9285714286
| 3w+5(w-8)=2(16+w) | | 3x+13=6x-2 | | 3h+16=7h-15 | | .5x^3-.125x= | | -3(-n+3)-10(9n+6)= | | 3x+12-9x=2(6-x) | | 4(m+3)=3(m-5) | | -14a+12=-16-7a | | .75(7-n)=12 | | 3/4(6+2)-1/4(6-2)= | | 2=a+b+(3-a-b) | | 6x-8=5x | | 3r^2-4r-2=0 | | x^3+4x^2-8x-8=0 | | 4-x=19+2x | | 3y+1=2x+4 | | 6(x+3)=-2x+66 | | 4/3(7-n)=12 | | 10x^8-28x^6-6x^5=0 | | -5(8+-3)= | | X(3x-5)(x-1)=0 | | 32/4=8 | | 18a^3+52a^6+5a= | | x^2+4x+4=3x+6 | | 8(3x-5)+20=68 | | 8=2(x+12) | | 4(x+4)=2(3x+2) | | 4d/=32/ | | 5n-2=3n+4 | | 6m-4(m+1)=14 | | 3b+5=8 | | 6x+10=3x-14 |